Community-Based Mangrove Ecotourism On Jeflio Island, Mayamuk District, Sorong District, Southwest Papua - Dwi Indah Widya Yanti; Ivonne M. Leiwakabessy (Median : Jurnal Ilmu Ilmu Eksakta, 2023)
The aim of the study was to analyze the value of coastal local wisdom of the indigenous people of Jeflio Island for the development of mangrove ecotourism. In the research method used qualitative and quantitative approaches. Data analysis includes analysis of local wisdom values. Based on research, the Jeflio community has local wisdom in the form of calls for conservation known in the form of recommendations such as "Nani Mi Wawolom Ti Eges Gu" (the native language of the Moi tribe), Pamali (prohibition) in certain areas/areas, Sasi - Customs and ceremonies," barapen" as well as local handicrafts such as making senate/mats, woven bags, "bayayai", boats, oars and spears. Local Wisdom Through Advice “Nani Mi Wawolom Ti Eges Gu” comes from the language of the Moi tribe which means protecting nature together. Local wisdom, such as local skills, traditional ceremonies and local values, is a cultural tourism attraction that can be empowered by tourism managers as creative industries to develop mangrove ecotourism to attract tourists and support local community economic development. One of the improvements in existing facilities in the Jeflio Mangrove Ecotourism Area is a souvenir shop that can be used to sell local Jeflio community crafts. In order to maintain and maintain the infrastructure of the Jeflio Mangrove Ecotourism Area, local wisdom values such as mutual cooperation and togetherness are very much needed. There are still weaknesses in the use of local wisdom in Jeflio because local wisdom owned by the community has not been legitimized.